Building on Tradition as the Way to Women’s Empowerment in Cambodia - World Bank (Washington, DC, 2012)
Approximately eighty percent of Cambodians live in rural areas with limited access to clean and affordable water and energy. Thirty-four percent of the rural population lives below the national poverty line on less than 2,367 riels ($0.60) per day. Even though Cambodia is a low income country, the cost of electricity is one of the world's highest due to limited domestic energy resources. Over ninety percent of energy used for cooking comes from wood and charcoal, contributing to increased deforestation. Women traditionally shoulder the burdens of collecting wood and cooking in Cambodian society. They to produce ceramic cook stoves with the goal of empowering women spend an average of three to four hours a day on energy-related activities such as gathering fuel wood, boiling water, and cooking. This report identified the unique role women play in rural Cambodian households, and describes a pilot initiative, reducing deforestation and pollution, and promoting healthier more vibrant communities.